Lysine methylation regulates the pRb tumour suppressor protein. - Munro, S; Khaire, N; Inche, A; Carr, S; La Thangue, N (2010)
The pRb tumour suppressor protein has a central role in coordinating early cell cycle progression. An important level of control imposed on pRb occurs through post-translational modification, for example, phosphorylation. We describe here a new level of regulation on pRb, mediated through the targeted methylation of lysine residues, by the methyltransferase Set7/9. Set7/9 methylates the C-terminal region of pRb, both in vitro and in cells, and methylated pRb interacts with heterochromatin protein HP1. pRb methylation is required for pRb-dependent cell cycle arrest and transcriptional repression, as well as pRb-dependent differentiation. Our results indicate that methylation can influence the properties of pRb, and raise the interesting possibility that methylation modulates pRb tumour suppressor activity.